راہ سلوک و تصوف کے بنیادی اصول و ضوابط کا ایک تجزیاتی مطالعہ: The Core Principles and Rules of Mysticism and Spiritual Journey: An Analytical Exploration - Chishti, Hassan Fareed; Munawar (Corresponding Author), Dr. Hifsa (Al-Irfan, 2025)
This dissertation presents an analytical study of the spiritual journey in Sufism, focusing on the path from self-realization to God-realization. It explores the core principles of Tasawwuf (Islamic mysticism), emphasizing the inner transformation of the soul through self-awareness, purification, and devotion. The research highlights how Sufism guides individuals to recognize their true selves, which leads to a deeper connection with the Divine. Through an in-depth analysis of Sufi teachings, practices, and the experiences of notable Sufi saints, the study demonstrates how self-knowledge serves as the foundation for attaining spiritual closeness to God. The work contributes to a broader understanding of spirituality in Islam and emphasizes the relevance of Sufi thought in modern times.